A Wish in the dark - Soontornvat, Christina (Melrose Park, Illinois : Candlewick Press, 2020)
All light in Chattana is created by one man- the Governor, who appeared after the Great Fire to bring peac and order to the city. For Pong, who was born in Namwon Prison, the magical lights represent freedom, and he dreams of the day he will be able to walk among them. But when Pong escapes from prison, he realizes that the world outside is just as unfair as the one behind bars. The wealthy dine and dance under bright lights while the poor toil away in darkness. Worst of all, Pong's prison tattoo marks him as a fugitive who can never be truly free. Nok, the prison warden's perfect daughter, is bent on tracking Pong down and restoring her family's good name. But as Nok hunts Pong through the alleys and canals of Chattana, she uncovers secrets that make her question the truths she has always held dear. Set in a Thai-inspired fantasy world, Christina Soontornvat's twist on Victor Hugo's Les Miserables is a dazzling, fast-paced adventure that explores the difference between law and justice- and asks whether one child can shine a light in the dark.